The relationship between family support system with maternal postpartum rage - Miftahul Fikri; Neviyarni Neviyarni; Afdal Afdal (Intelektual Pustaka Media Utama, 2023)
This study investigated the mediating effect of social support with postpartum rage on young mothers during the first to twenty-four months. Method in this research is c a cross-sectional survey design was used in this quantitative non-experimental research. Subject of young mothers who have delivered the children aged one to twenty-four months women who lived in the area of west Sumatera. This study used edinburgh postnatal depression scale (EPDS) to measure which focuses on postpartum rage and the social support system scale to measure social support. Data analysis spearman Rho correlation, analysis of variance (ANOVA) test and path coefficients. After data from 121 participants were analyzed, the results of measurement showed a significant difference between postpartum rage that occurred in the group of young mothers who had their first child, which was greater than those who had a second or third child. Pregnancy has a partially mediating effect on the relationship between anger during pregnancy and postnatal depression in the first month. Findings highlight the importance of social support with high postpartum rage and provide interventions to increase their social support.